Leadership Style in Disciplining Financial Administration in Elementary Schools - Azaluddin (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
This study aims to analyze the principal's leadership style in disciplining financial administration at Kaobula 1 Elementary School. Orderly and transparent financial administration is an important element in supporting the quality of education. However, the implementation of financial management often faces challenges such as lack of discipline, low administrative competence, and minimal supervision. A qualitative approach with a case study method was used in this study. Data were obtained through in-depth interviews, direct observation, and document studies. The results of the study indicate that the principal uses a transformational leadership style, in which he provides motivation, role models, and a clear vision to administrative staff. The principal also applies routine supervision and accountability-based management to ensure compliance with rules and efficiency in financial management. In addition, active participation from all stakeholders, such as teachers and school committees, helps strengthen the internal control system. This study concludes that an effective leadership style, oriented towards collaboration and integrity, can improve financial administration discipline. Recommendations are given to the school to continue to develop financial management training and strengthen the monitoring and evaluation system on an ongoing basis.